Portrait of Social Inequality and Family Crisis in Mirāth by Muhammad Husayn Haykal: Literary Realism Approach - Husnul Khotimah; Misbahus Surur (Journal of Arabic Literature (JaLi), 2026)
As a mimetic cultural artifact, literary conflict frequently encodes the socio-political tensions and ideological fractures of its originating society. Within the framework of literary realism, this study critically interrogates the representation of social inequality and familial disintegration in Muhammad Husayn Haikal's short story "Mirāth," which is featured in his collection Qiṣaṣ Miṣriyya (first published in 1969 and republished by Muassasah Handawi in 2014). Departing from purely formalist readings, this research argues that Haikal's narrative conflicts serve as a diagnostic lens through which the structural asymmetries of early twentieth-century Egyptian society are laid bare. Employing a descriptive qualitative methodology, data were gathered via close reading, translation, and systematic note-taking, subsequently analyzed using the Miles and Huberman interactive model. The findings delineate four interlocking tropes of social reality: structural inequality, gender asymmetry, domestic discord, and moral erosion. Collectively, these elements substantiate the short story's function not merely as a literary reflection, but as a critical social document. The study ultimately contends that the story's depiction of mismanagement in inheritance and waqf (endowment) systems operates as a catalytic agent of protracted communal strife, thereby contributing to broader scholarly discourses on the intersection between Arabic realist narrative and socio-economic critique.